2018
DOI: 10.1302/1863-2548.12.170174
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of an anteverting triple periacetabular osteotomy for the treatment of hip instability in down syndrome

Abstract: PurposeTo investigate the outcomes of an anteverting triple periacetabular osteotomy for the treatment of hip instability in skeletally immature patients with Down syndrome.MethodsWe evaluated 16 patients (21 hips) with Down syndrome and hip instability who underwent an anteverting triple periacetabular osteotomy between 2007 and 2016. There were nine females and seven males with an average age of 7.4 years SD 2.0. We assessed the level of hip pain, gait ability and clinical stability at a minimum of one year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This current study as well as prior literature demonstrate that maintaining a reduced hip can be difficult to achieve without complications. [5][6][7][8][9][10] Surgeons must balance the patient's hypotonia, ligamentous laxity, and variable degrees of coxa valga, femoral anteversion, relative acetabular retroversion and acetabular undercoverage. Prior literature has suggested that focusing on just the soft tissue, or just the femoral malrotation, leads to an unacceptable failure rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This current study as well as prior literature demonstrate that maintaining a reduced hip can be difficult to achieve without complications. [5][6][7][8][9][10] Surgeons must balance the patient's hypotonia, ligamentous laxity, and variable degrees of coxa valga, femoral anteversion, relative acetabular retroversion and acetabular undercoverage. Prior literature has suggested that focusing on just the soft tissue, or just the femoral malrotation, leads to an unacceptable failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…4 Management of these patients is not for the inexperienced or ill-equipped surgeon given its high complication rate, even in the most experienced hands. [5][6][7][8][9][10] Unfortunately, there is a paucity of literature to guide management.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…12 Multiple interventions for hip instability in children with DS, including closed reduction and several surgical techniques, have been described over the years, often showing suboptimal outcomes and considerable complication rates. [13][14][15][16][17][18][19][20][21][22] In 1959 and 1964, Sharrard 23,24 described a posterior iliopsoas transfer of the tendon insertion for the treatment of paralytic dislocation of the hip in patients with meningomyelocele and cerebral palsy, showing positive results in 17/22 patients. The Sharrard procedure transfers the iliopsoas muscle tendon insertion from the trochanter minor to the trochanter major through a foramen in the ala iliaca (Fig.…”
Section: Introductionmentioning
confidence: 99%